McGraw-Hill concise encyclopedia of science & technology. - McGraw-Hill Publishing Company (New York : McGraw-Hill, 2009)
Features more than seven thousand entries covering topics, terms, and concepts in math, science, and technology.
v. 1. A-L -- v. 2. M-Z.
"This material was extracted from the McGraw-Hill encyclopedia of science & technology, 10th ed., c2007"--T.p. verso.
Includes bibliographical references and index.
english
Keywords: science -- encyclopedias; technology -- encyclopedias